Population pharmacokinetics of rilpivirine following oral administration and long-acting intramuscular injection in real-world people with HIV - Thoueille, Paul; Saldanha, Susana Alves; Schaller, Fabian; Choong, Eva; Veuve, François; Munting, Aline; Cavassini, Matthias; Braun, Dominique; Günthard, Huldrych F.; Duran Ramirez, Jessy J.; Surial, Bernard; Furrer, Hansjakob; et al. (Frontiers in Pharmacology, 2024)
The pharmacokinetics of long-acting rilpivirine has mostly been studied in clinical trials, which do not fully address the uncertainties that arise in routine clinical situations. Our population analysis aims to establish percentile curves for rilpivirine concentrations in people with HIV (PWH) followed-up in a routine clinical setting, while identifying patient-related factors that may influence rilpivirine exposure. A total of 238 PWH enrolled in our nationwide multicenter observational study contributed to 1038 concentrations (186 and 852 concentrations after oral and intramuscular injection, respectively). Rilpivirine pharmacokinetics were best described by a twocompartment model with an oral to intramuscular relative bioavailability factor. A simple zeroorder absorption process was retained for oral administration while a parallel first-order absorption was used for intramuscular administration, with 27.6% of the dose released via a fast absorption pathway and the remaining fraction via a slow absorption pathway. Our model estimated that longacting rilpivirine reaches steady-state after 2.5 years and has an elimination half-life of 18 weeks, consistent with published estimates. In females, a 45.6% reduction in the proportion of the dose absorbed via the rapid absorption pathway was observed. However, this resulted in no more than 15% difference in trough concentrations (Ctrough) compared to males, which was not considered to be clinically relevant. Overall, our model-based simulations showed that only approximately 50% of long-acting rilpivirine Ctrough would be above the 50 ng/mL threshold associated with optimal therapeutic response, while approximately 85% of Ctrough would be above the first quartile of concentrations observed in Phase III trials (32 ng/mL).